FBXO38 Ubiquitin Ligase Controls Sertoli Cell Maturation - Dibus, Nikol; Zobalova, Eliska; Monleon, Mario A. M.; Korinek, Vladimir; Filipp, Dominik; Petrusova, Jana; Sedlacek, Radislav; Kasparek, Petr; Cermak, Lukas (Frontiers in Cell and Developmental Biology, 2022)
The ubiquitin ligase SCFFBXO38 controls centromeric chromatin by promoting the degradation of the ZXDB protein. To determine the importance of this pathway during development, Fbxo38-deficient mice were generated. The loss of FBXO38 resulted in growth retardation affecting several organs, including the male reproductive system. A detailed analysis of the mutant testes revealed pathological changes in the seminiferous tubules, accompanied by a significant decrease in sperm production and reduced fertility. In adult testes, FBXO38 was specifically expressed in Sertoli cells, a somatic population essential for spermatogenesis initiation and progression. Sertoli cells lacking FBXO38 exhibited stabilized ZXDB protein and upregulated centromeric chromatin. Furthermore, the gene expression profile revealed that the absence of FBXO38 led to a defect in Sertoli cell maturation, specifically characterized by dysregulation in genes controlling retinoic acid metabolism and intercellular communication. Consequently, we documented significant changes in their ability to initiate spermatogonial differentiation. In conclusion, we show that FBXO38 acts as a Sertoli cell maturation factor, affecting the Sertoli cell transcription program, centromere integrity, and, subsequently, the ability to control spermatogenesis.